1989
DOI: 10.1136/hrt.62.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Value and limitations of adenosine in the diagnosis and treatment of narrow and broad complex tachycardias.

Abstract: SUMMARY The diagnostic and therapeutic potential of intravenous adenosine was studied in 64 patients during 92 episodes of regular sustained tachycardia. In 40 patients who had narrow complex tachycardias (QRS <0-12 s) adenosine (2-5-25 mg) restored sinus rhythm in 25 with junctional tachycardias (46 of 48 episodes) and produced atrioventricular block to reveal atrial or sinus tachycardia in 15. In 24 patients with broad complex tachycardias (QRS > 0 12 s) adenosine terminated the tachycardias in six patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(41 citation statements)
references
References 25 publications
1
38
0
2
Order By: Relevance
“…350 Adenosine Adenosine may aid in diagnosing VT, but it will not terminate it (LOE 4). 351,352 Calcium Channel Blockers The evidence for the use of calcium channel blockers in VT is conflicting, with most studies opposing their use (LOE 4), 353354,355 but 1 study supported the use as long as coronary disease was not present (LOE 5). 356 …”
Section: Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…350 Adenosine Adenosine may aid in diagnosing VT, but it will not terminate it (LOE 4). 351,352 Calcium Channel Blockers The evidence for the use of calcium channel blockers in VT is conflicting, with most studies opposing their use (LOE 4), 353354,355 but 1 study supported the use as long as coronary disease was not present (LOE 5). 356 …”
Section: Magnesiummentioning
confidence: 99%
“…Five studies involving more than 300 patients (LOE 4) 351,352,[373][374][375] demonstrated that adenosine could safely be administered in regular wide-complex tachycardia: it converted wide-complex tachycardia secondary to supraventricular tachycardia to normal sinus rhythm, but rarely terminated VT. One small study showed poor rates of conversion to sinus rhythm in patients known to have VT (LOE 4). 344 No patient in these trials had serious adverse events; however, there are case reports in patients with irregular wide-complex tachycardia (generally pre-excited atrial fibrillation) in whom VF was precipitated by adenosine (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Premature isolated atrial and ventricular complexes are often observed after adenosine-induced termination of tachycardias' 1 '. The rare occurrence of short runs of ventricular tachycardias has been quoted' 2 ' 31 , but no serious consequences of this proarrhythmic effect have been reported' 4 '. Despite extensive research on the cardiac and cardiovascular effects of adenosine 13 ', the pathophysiological mechanism of the premature ventricular contractions that develop after adenosine-induced termination of a supraventricular tachycardia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it might be expected that the drug exerts almost no antiarrhythmic effects on primary atrial tachyarrhythmias (i.e., atrial fibrillation and atrial flutter) as well as intraatrial reentrant and automatic atrial tachycardia [58,77]. Termination of atrial flutter and focal atrial tachycardia, however, has occasionally been reported [60,66,77]. It has been shown that adenosine is capable of terminating sinus node reentrant tachycardia and atrial tachycardia owing to triggered activity.…”
Section: Atrial Tissuementioning
confidence: 97%